The trans-Tasman economic relationship: Like ham and eggs? "The chicken has an interest but the pig is committed" - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2003)
This paper sets out to examine the factors that need to be considered before New Zealand enters into negotiations over further integration in the trans-Tasman market. While it is timely to look forward to the shape of possible future integration, it is also important to understand the lessons of New Zealand's past economic relationship with Australia. In particular, an examination of landmark Australia New Zealand Closer Economic Relationship Agreement (known as CER) signed in 1983 forms the basis of this paper. CER is at the cornerstone not only of New Zealand's relationship with Australia but is also a key part of New Zealand's trade policy. Therefore a stock take of the trans-Tasman relationship is timely because: [1] sufficient time has past since the CER agreement was signed; [2] major trade initiatives (APEC) and agreements (Uruguay Round Agreement, Singapore CEP) have been signed; and [3] there has been an intensification of the processes of globalisation and localisation. Specifically, the aim of the paper is to examine the trans-Tasman relationship through the lens of institutional economics to tease out the important economic issues associated with integration. To accomplish this, careful case-by-case investigation of each area of trans-Tasman contact is necessary.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Handelsregionalismus; Neuseeland; Australien